2017
DOI: 10.22605/rrh3893
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ use of and attitudes towards self-medication in rural and remote Slovenian family medicine practices: a cross-sectional multicentre study

Abstract: A B S T R A C TIntroduction: Self-medication is very common in the general population, but its prevalence can differ according to the place of residence. The aim of this study was to determine the prevalence of self-medication in patients attending rural and remote family physicians, and to detect the important factors that are associated with it. Methods: A cross-sectional multicentre study was performed in 24 rural and remote family medicine practices in Slovenia was performed. The aim was to include 720 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…The use of medicines without physician supervision for diagnosis and/or treatment 32,33 is a common problem and one of the health concerns worldwide. Despite several efforts to reduce SM, the practice of SM is significantly higher among developing countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of medicines without physician supervision for diagnosis and/or treatment 32,33 is a common problem and one of the health concerns worldwide. Despite several efforts to reduce SM, the practice of SM is significantly higher among developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SM among Iranian household in the last month was found to be 18.2%. The magnitude of SM practice was found to be 23.3% in Egypt, 35 51% in Slovenia, 32 25.4% in the United States, 36 27.5% in Kuwait, 37 7.3% in Indonesia, and 11.9% in India. 38,39 The reasons for the variation in the practice of SM across different countries and regions could be due to the levels of awareness about the rational use of drugs, accessibility of modern health facilities, cultural preferences and beliefs of the study participants.…”
Section: Dovepressmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients are dissatisfied because they wait long for health services, are far from their physicians, and sometimes working hours of doctor’s office do not suit them [ 46 , 47 ]. Reasons for self-care lie also in patient’s distrust of physicians, while, on the other hand, patients sometimes do not want to bother physicians, particularly if the cause of pain is already known [ 48 ]. The self-care is also a method of choice in cases where conventional medicine failed, or its methods have already been exhausted.…”
Section: Discussionmentioning
confidence: 99%
“…According to results of Nagarajaiah et al [ 36 ], important sources of information about self-care with medications are family members and relatives, followed by healthcare providers and pharmacists. A study carried out in Slovenia demonstrated that relatives and pharmacists were the most common sources of information and tips about self-care, and that self-care was more frequent among younger subjects and those with higher educational level [ 48 , 58 ].…”
Section: Discussionmentioning
confidence: 99%